Elevated serum beta-2 microglobulin level predicts short-term poor prognosis of patients with de novo acute omicron variant COVID-19 infection - Gong, Shengping; Ma, Ruishuang; Zhu, Ting; Ge, Xiaoqin; Xie, Rongrong; Tao, Qingsong; Shi, Cong (Frontiers in Cellular and Infection Microbiology, 2023)
The devastating coronavirus disease of 2019 (COVID-2019) epidemic has beenis declared a public health emergency, resulting in a worldwide pandemic. The Oomicron variety is the most common epidemic mutant strain in the globe. Serum beta-2 microglobulin (β2-MG) iswas associated with endothelial cell injury and has value in monitoring the progression of inflammation in infected individuals. Nonetheless, the potential functions of β2-MG in omicron remain elusive.We retrospectively analyzed a cohort of 240 individuals with omicron to explore To investigate the prognostic value of serum β2-MG levels at diagnosis., we retrospectively analyzed a cohort of 240 people with omicron. Over the course of 65 days, Aall patients were monitored, followed up for 65 days, and death was the primary outcome was death. Patients were allocated to two groups: those with divided into the high β2-MG group and the low β2-MG levels group. OS was analyzed using tThe Kaplan-Meier method was used to examine OS, and were compared using the long-rank test was used to compare them. Univariate and multivariate Cox hazard models were used to determine the prognostic significance.Our results revealed that β2-MG was significantly elevated in omicron. β2-MG levels in severe patients were higher than in mild-to-moderate patients, and the difference was statistically significant. Timely, interleukin-6 (IL-6) and interleukin-10 (IL-10) were observed to be significantly increased in individuals exhibiting elevated levels of in patients with high β2-MG.Besides, patients exhibiting elevated levels of with high β2-MG levels had significantly shorter demonstrated a statistically significant decrease in overall survival (OS, P < 0.0001). An elevated β2-MG level (≥ 4.72 mg/L) was found to be an independent, adverse prognostic factor for OS in omicron patients, according to multivariate Cox proportional hazards regression analysis (P = 0.001).Conclusions: Serum β2-MG level at initial diagnosis was significantly correlated with omicron severity and prognosis. Thus, we propose that β2-MG may be an independent poor additional prognostic factor in patients with omicron.